Variants of string assembling systems - Kutrib, Martin; Wendlandt, Matthias; Justus Liebig University Giessen (My University, 2024)
String assembling systems are biologically inspired mechanisms that generate strings from copies out of finite sets of assembly units. The underlying mechanism is based on piecewise assembly of a double-stranded sequence of symbols, where the upper and lower strand have to match. The generation is additionally controlled by the requirement that the first symbol of a unit has to be the same as the last symbol of the strand generated so far, as well as by the distinction of assembly units that may appear at the beginning, during, or at the end of the assembling process and by a length restriction on the units. We investigate the power of these model-inherent control mechanisms by considering variants where one or more of these mechanisms are relaxed. The generative capacities and the relative power of the variants are our main interest. In particular, we prove that the power gained in the different control mechanisms may yield strictly more powerful systems and incomparable capacities. Additionally, we generalize these systems to multi-stranded systems. We obtain a strong connection to one-way multi-head finite automata and show an infinite, dense, and strict strand hierarchy. Finally, we examine the closure properties of the different variants of string assembling systems.
Keywords: String assembling; Double-stranded sequences; Stateless; Two-head finite automata; Decidability; Closure properties; ddc:510; ddc:004